Analysis of The Meaning of Sylvia Plath’s Poems Which Reflected To Her Life and Death : A Language Stylistics Analysis - Amelia Yuli Astuti; Chalesti Chalesti (Jurnal Ilmiah Langue and Parole, 2022)
This research uses literary work as the object of research. The literary works analyzed in this research are five poems by Sylvia Plath entitled Daddy, Ariel, Poppies in October, Lady Lazarus, and Edge. The aims of this research to showing the languange features in Plath’s poem and revealing the meaning through languange features using in Plath’s poem. To find out the languange feature in the Plath’s poems it used level languange in Stylistics consist of phonologycal level and semantic level. The phonological level consist of alliteration, assonance, and consonance. And semantic level consist of simile, personification, methapor, imagery, hyperbole, and symbol.This research using pragmatic approach to revealing the meaning in Plath’s poems and features languange as a reference to help in finding meaning in each stanza of the poem. This research uses descriptive qualitative method and the technique use content analysis technique. This is because this research will analyses the all content in Plath’s poems.